2016
DOI: 10.1002/elan.201600231
|View full text |Cite
|
Sign up to set email alerts
|

Two Novelties in Ion‐pair Formation‐based Potentiometric Titrations of Anionic Surfactants

Abstract: Two novel approaches in ion‐pair formation‐based potentiometric titrations of anionic surfactants are presented. First, a new type of the low ohmic coated‐wire ion‐selective electrode is introduced; the polymeric membrane containing a plasticizer mixed with carbon powder. Second, didecyldimethylammonium chloride as the cationic titrant is for the first time proposed and applied, providing the titration curves with the highest potential jump.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The titration of ionic surfactants is based on the reaction of two oppositely charged large lipophilic ions resulting in the formation of a sparingly soluble ion-associate that becomes extractable into the membrane. Mikysek et al reported on a low resistive (10 Ω) coated-wire ion-selective electrode for the potentiometric detection of anionic surfactants . The electrode was prepared by dipping an Al conductor into a homogenized mixture of the graphite powder, PVC, and NPOE in THF.…”
Section: Analytical Applications and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The titration of ionic surfactants is based on the reaction of two oppositely charged large lipophilic ions resulting in the formation of a sparingly soluble ion-associate that becomes extractable into the membrane. Mikysek et al reported on a low resistive (10 Ω) coated-wire ion-selective electrode for the potentiometric detection of anionic surfactants . The electrode was prepared by dipping an Al conductor into a homogenized mixture of the graphite powder, PVC, and NPOE in THF.…”
Section: Analytical Applications and Methodologiesmentioning
confidence: 99%
“…Mikysek et al reported on a low resistive (10 Ω) coated-wire ion-selective electrode for the potentiometric detection of anionic surfactants. 185 The electrode was prepared by dipping an Al conductor into a homogenized mixture of the graphite powder, PVC, and NPOE in THF. In this work, didecyldimethylammonium chloride was used as a cationic titrant to provide titration curves with a larger potential jump than ones obtained with conventionally used titrants.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Ion pairing of cationic surfactants with anionic ones is generally known and practically used for their titration with potentiometric indication, which enables us to determine their total contents [ 21 ]. Here, a two-stage accumulation performed ex-situ was used to modify the CPE surface with a double layer of mutually paired surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…Equations ( 1) and ( 2) represent the DAC 2+ /Na + -exchange reaction and the expression for the exchange coefficient, respectively. These equations are analogous to the well-known extraction equilibria and extraction constants utilized in conventional titrations based on ion pair formation [27,28].…”
Section: Complexometric Potentiometric Titration and Response Mechanismmentioning
confidence: 97%